Preparation method of microporous 3D printing polylactic acid scaffold

By adding inorganic salt particles to polylactic acid stock solution and constructing microporous polylactic acid scaffolds using a template etching method, the problem of the difficulty in preparing microporous structures in the prior art has been solved, and efficient, low-cost, and biocompatible microporous polylactic acid scaffolds have been prepared.

CN123038342APending Publication Date: 2026-11-06DALIAN UNIV OF TECH +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510576606.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-05-06
Publication Date
2026-11-06

AI Technical Summary

Technical Problem

Existing technologies make it difficult to prepare 3D printed polylactic acid scaffolds with uniform micropores, controllable density, and uniform size in a simple and low-cost manner. Moreover, existing methods are complex, costly, and difficult to achieve efficient microporous structure construction.

Method used

By adding inorganic salt particles to a polylactic acid organic solution and stirring, a polylactic acid stock solution was prepared. Then, the solution was incubated in an aqueous etching solution using a template etching method to construct a microporous polylactic acid scaffold.

Benefits of technology

The method for preparing polylactic acid scaffolds with uniform micropores and pore size is simple, low-cost, does not require expensive instruments, has good biocompatibility, and is suitable for a variety of biomedical applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005388764230000011
    Figure HDA0005388764230000011
  • Figure HDA0005388764230000021
    Figure HDA0005388764230000021
  • Figure HDA0005388764230000022
    Figure HDA0005388764230000022
Patent Text Reader

Abstract

This invention discloses a method for preparing microporous 3D-printed polylactic acid (PLA) scaffolds. The method comprises two steps: the first step involves adding inorganic salt particles to an organic solution of PLA and stirring to obtain a PLA stock solution containing inorganic salt particles; the second step involves 3D printing the PLA stock solution using a template dissolution method in an aqueous etching solution, thereby achieving a microporous 3D-printed PLA scaffold. This invention provides a method for physically creating pores in PLA materials by changing the inorganic salt particles, organic solvent, and aqueous etching solution. It is considered a green, controllable, and highly promising method for creating pores in PLA materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a method for preparing a 3D printing polylactic acid stock solution containing inorganic salt particles, and then a method for constructing a microporous polylactic acid scaffold for biomedicine using a template etching method. Technical Background

[0002] Polylactic acid (PLA) is widely used because the biomaterials prepared from it are low-cost, recyclable, and biocompatible. PLA materials can be 3D printed into scaffolds of various shapes, and their excellent physicochemical properties have wide applications in biomedicine, such as vascular scaffolds, tissue engineering materials, bone repair materials, and medical dressings. For example, the Igaki-Tamai scaffold is a biodegradable vascular scaffold designed using PLLA (poly-L-lactic acid) as its material, promoting vascular endothelialization, inhibiting smooth muscle cell proliferation, and reducing the risk of restenosis and thrombosis. 3D-printed porous PLA can be used to manufacture bone screws, bone graft materials, etc., promoting bone tissue repair and regeneration. The most important aspect of 3D-printed PLA scaffolds in biomedicine is the fabrication of microporous structures. Microporous structure and porosity are crucial to cell behavior and health. For example, 3D bioprinted scaffolds in tissue engineering applications typically provide structural support and a suitable microenvironment to support cell behavior. Microporous structures are beneficial for cell adhesion and development, and are extremely helpful for tissue repair. Microporous structure and porosity are crucial to cell behavior and health. 3D bioprinted scaffolds should have a highly porous and interconnected pore network structure to facilitate nutrient transport, waste excretion, and cell growth, proliferation, and differentiation.

[0003] Currently, commonly used methods for preparing microporous PLA materials include the following: 1) Using solvent-free carbon dioxide solid-state foaming technology, polylactic acid scaffold materials with pore sizes of 350-20 μm were prepared under different saturation pressures. This method utilizes carbon dioxide as a physical foaming agent to form a microporous structure in PLA materials. 2) Combining 3D printing and freeze-drying technologies to fabricate polylactic acid-pearl-chitosan-copper (PLA-P-CS / Cu) scaffolds with a dual-scale porous structure. This method conveniently constructs polylactic acid-polytrimethylene carbonate (PLMC) bioactive scaffolds with multi-scale composite porous structures and multifunctional properties through freeze-drying and 3D printing of HIPEs (high internal phase emulsions). However, the above two methods are complex, costly, and require sophisticated instruments, making it difficult to achieve 3D-printed polylactic acid scaffolds with uniform micropores, controllable density, and uniform size. Therefore, there is an urgent need to develop simple and green methods adapted to PLA materials for pore formation. Summary of the Invention

[0004] To address the problems of existing technologies, this invention proposes a method for preparing microporous 3D printed polylactic acid scaffolds. First, a 3D printed polylactic acid stock solution containing inorganic salt particles is prepared, and then a microporous polylactic acid scaffold for biomedicine is constructed by a template etching method.

[0005] A method for preparing a microporous 3D-printed polylactic acid scaffold, the method comprising the following steps:

[0006] Step 1: Add inorganic salt particles to the organic solution of polylactic acid and stir to obtain a polylactic acid stock solution containing inorganic salt particles, which is the polylactic acid stock solution for 3D printing.

[0007] Step 2: The polylactic acid stock solution obtained in step (1) is used to obtain a polylactic acid scaffold adapted for the application by 3D printing. The polylactic acid scaffold is incubated in an aqueous etching solution using the template dissolution method, thereby preparing a microporous 3D printed polylactic acid scaffold.

[0008] In the preferred embodiment of the above-described technical solution, the polylactic acid material can be polylactic acid of various molecular weights (10k-200k), such as dextrorotatory polylactic acid (PDLA), levorotatory polylactic acid (PLLA), racemic polylactic acid (PDLLA), and non-optically active polylactic acid (Meso-PLA).

[0009] In the preferred embodiment of the above-described technical solution, the organic solvent in the organic solution includes one or more of methanol, ethanol, acetonitrile, acetone, diethyl ether, N,N-dimethylformamide, dimethyl sulfoxide, and dichloromethane, preferably one or two of acetonitrile and dichloromethane.

[0010] In the preferred embodiment of the above-described technical solution, the inorganic salt includes one or more of sodium chloride, calcium carbonate, copper sulfate, potassium nitrate, sodium bicarbonate, magnesium sulfate, iron oxide, calcium phosphate, and potassium chloride, preferably one or two of sodium bicarbonate and sodium chloride.

[0011] In the preferred embodiment of the above-described technical solution, the aqueous etching solution comprises one or more solutions selected from hydrochloric acid, sulfuric acid, nitric acid, phosphoric acid, acetic acid, citric acid, sodium hydroxide, ammonia, sodium carbonate, sodium bicarbonate, sodium acetate, sodium hypochlorite, sodium phosphate, and sodium sulfite, preferably one or more solutions selected from hydrochloric acid, sodium hydroxide, and ammonia.

[0012] In the above-described technical solution, preferably, the ratio of polylactic acid material to organic solvent in the polylactic acid organic solution is 0.1–20 mg: 20 mL, preferably 1–10 mg: 20 mL; the ratio of the 3D-printed polylactic acid material (polylactic acid scaffold) to the aqueous etching solution is 0.1–200 mg: 20 mL, preferably 1–10 mg: 20 mL.

[0013] In the above-described technical solution, preferably, the concentration of the inorganic salt in the organic solution of polylactic acid is 0.1–20 mg / mL, preferably 0.5–5 mg / mL; and the concentration of the aqueous etching solution is 1–2000 mM, preferably 10–500 mM.

[0014] In the above-described technical solution, in the preferred case, in the first step, the temperature at which the organic salt is stirred in the polylactic acid organic solution is 0–80°C, preferably 10–40°C; in the second step, the incubation temperature of the aqueous etching solution is 0–60°C, preferably 10–50°C.

[0015] In the above-described technical solution, in the preferred case, in the first step, the inorganic salt is stirred in the polylactic acid organic solution for 1 to 96 hours, preferably 6 to 48 hours; in the second step, the aqueous etching solution is incubated for 1 to 48 hours, preferably 12 to 24 hours.

[0016] In the preferred embodiment of the above-described technical solution, the inorganic salt particles have a particle size of 10-50 μm and are obtained by grinding the inorganic salt particles.

[0017] In the preferred embodiment of the above-described technical solution, the polylactic acid stock solution obtained in step (1) is dried to remove the organic solvent, and then the dried polylactic acid stock solution is 3D printed to obtain a polylactic acid scaffold. The drying conditions are: temperature 40-80℃, time 1h-12h.

[0018] The microporous 3D printed polylactic acid scaffold prepared by the above method has a pore size of 100-200 nm.

[0019] This invention provides a method for physically creating pores in polylactic acid (PLA) materials by modifying inorganic salt particles, organic solvents, and aqueous etching solutions, exhibiting high mechanical strength and stability of the scaffold. It is considered a green, controllable, and highly promising method for creating pores in PLA materials.

[0020] Beneficial effects:

[0021] The method for preparing microporous 3D printed polylactic acid scaffolds described in this invention has the following advantages over other methods:

[0022] (1) Polylactic acid scaffolds have stable physical and chemical properties and can be used in a variety of scenarios;

[0023] (2) This method produces uniform micropores, is simple, and does not involve expensive equipment;

[0024] (3) The polylactic acid scaffold has uniform micropore size;

[0025] (4) Polylactic acid stock solution has good printability and can meet different printing and size requirements;

[0026] (5) It has good biocompatibility. No toxic chemicals are used in the whole process, which ensures the biodegradability and biocompatibility of polylactic acid scaffold.

[0027] In summary, this method is a simple, controllable, widely applicable, and environmentally friendly method for preparing 3D printed microporous polylactic acid scaffolds. Attached Figure Description

[0028] Figure 1 : The prepared polylactic acid stock solution.

[0029] Figure 2 Polylactic acid scaffolds obtained by 3D printing polylactic acid stock solution.

[0030] Figure 3 Distribution of inorganic salts in 3D printed polylactic acid materials.

[0031] Figure 4 Scanning electron microscopy characterizes polylactic acid scaffolds.

[0032] Figure 5 Tomographic scanning characterizes lactic acid scaffolds printed from inorganic salt stock solutions of different concentrations.

[0033] Figure 6 Tomographic scanning characterizes lactic acid scaffolds incubated with different aqueous etching solutions.

[0034] Figure 7 Tomographic scanning characterizes lactic acid scaffolds incubated with aqueous etching solutions of different concentrations.

[0035] Figure 8 Nanoindentation instruments characterize the mechanical strength of the support. Detailed Implementation

[0036] This invention provides a method for preparing microporous, protein-coupling-active 3D-printed polylactic acid (PLA) materials. The method involves dissolving various molecular weight PLAs, including dextrorotatory polylactic acid (PDLA), levorotatory polylactic acid (PLLA), racemic polylactic acid (PDLLA), and optically inactive polylactic acid (Meso-PLA), in 20 mL of an organic solution. Then, 0.1–20 mg of ground inorganic salt particles are added, and the mixture is stirred at 0–80 °C for 1–96 h to obtain a PLA stock solution. The dried PLA stock solution is then used for 3D printing to obtain PLA scaffolds of different shapes. 0.1–200 mg of the PLA scaffold is then placed in 20 mL of a 1–2000 mM aqueous etching solution and treated at 0–60 °C for 1–48 h.

[0037] The following specific embodiments are for further explanation of the content of the present invention and should not be construed as limiting the present invention in any way.

[0038] Example 1: Preparation of polylactic acid stock solution

[0039] Three 5mg portions of racemic polylactic acid (50kDa) were dissolved in 20mL of dichloromethane. 1, 2, and 5mg of ground sodium bicarbonate particles (50μm) were added to each, respectively. The mixtures were stirred at 20℃ for 6 hours to obtain three polylactic acid stock solutions. Figure 1 The image shown is of a polylactic acid stock solution containing ground sodium bicarbonate particles, which gradually turns white as the amount of sodium bicarbonate particles added increases.

[0040] Example 2: Polylactic acid scaffold obtained by 3D printing of polylactic acid stock solution

[0041] Three 5mg portions of racemic polylactic acid (PLA) material (50kDa) were dissolved in 20mL of dichloromethane, respectively. 1, 2, and 5mg of ground sodium bicarbonate particles with a particle size of 50μm were added to each, and the mixtures were stirred at 20℃ for 6 hours, then dried in an oven at 60℃ for 3 hours to obtain three PLA stock solutions. The three PLA stock solutions were then 3D printed to obtain corresponding PLA scaffolds, each scaffold having a thickness of 3.2mm and a length and width of 8mm (e.g., ...). Figure 2 (As shown). The particle distribution of inorganic salts within the filament diameter of polylactic acid with 2 mg of ground sodium bicarbonate particles of 50 μm in diameter is shown in the figure. Figure 3As shown, the black granular material is printed sodium bicarbonate particles. Due to the high-temperature printing, the scaffold turns dark brown. Adding 1 mg of ground sodium bicarbonate particles with a diameter of 50 μm results in a more dispersed distribution of sodium bicarbonate particles compared to adding 2 mg. Adding 5 mg of ground sodium bicarbonate particles with a diameter of 50 μm results in a denser distribution of sodium bicarbonate particles compared to adding 2 mg.

[0042] Example 3: Scanning electron microscopy characterization of polylactic acid scaffold

[0043] 5 mg of racemic polylactic acid (50 kDa) was dissolved in 20 mL of dichloromethane. 5 mg of ground sodium bicarbonate particles with a particle size of 50 μm were added. The mixture was stirred at 20 °C for 6 h and then dried in an oven at 60 °C for 3 h to obtain three polylactic acid stock solutions. The obtained polylactic acid stock solutions were then printed using 3D printing technology to obtain corresponding polylactic acid scaffolds. The scaffolds had a thickness of 3.2 mm and dimensions of 8 mm in both length and width. 100 mg of the polylactic acid scaffold was immersed in 20 mL of 500 mM hydrochloric acid etching solution at 45 °C for 24 h. After repeated washing with deionized water and drying, the treated polylactic acid scaffold was obtained and imaged using a scanning electron microscope. Figure 4 As shown, after the polylactic acid scaffold is etched with hydrochloric acid solution, the sodium bicarbonate particles inside dissolve and form a uniform microporous structure on the surface with a pore size of 100 nm.

[0044] Example 4: Tomographic characterization of lactic acid scaffolds printed with inorganic salt stock solutions of different concentrations

[0045] Five 5 mg portions of racemic polylactic acid (PLA) material (50 kDa) were dissolved in 20 mL of dichloromethane. 0.1, 0.5, 1, 2, and 5 mg of ground sodium bicarbonate particles with a particle size of 50 μm were added respectively. The mixture was stirred at 20 °C for 6 h and then dried in an oven at 60 °C for 3 h to obtain five PLA stock solutions. The five PLA stock solutions were then 3D printed to obtain corresponding PLA scaffolds. The scaffolds had a thickness of 3.2 mm and a length and width of 8 mm. A PLA scaffold prepared without sodium bicarbonate particles was used as a control group. 100 mg of each of the above PLA scaffolds was then treated in 20 mL of 500 mM hydrochloric acid etching solution at 45 °C for 24 h. Figure 5 As shown, the porosity of the scaffold was calculated using tomographic scanning. The porosity of the polylactic acid scaffold without sodium bicarbonate particles was 51%. The porosity increased continuously with the addition of sodium bicarbonate particles. The polylactic acid scaffold with 5 mg of sodium bicarbonate particles exhibited the highest porosity, at 68%.

[0046] Example 5: Tomographic characterization of lactic acid scaffolds incubated with different aqueous etching solutions

[0047] Three 5mg portions of racemic polylactic acid (PLA) material (50kDa) were dissolved in 20mL of dichloromethane. 5mg of ground sodium bicarbonate particles with a particle size of 50μm were added, and the mixture was stirred at 20℃ for 6 hours, followed by drying in a 60℃ oven for 3 hours to obtain three PLA stock solutions. The three PLA stock solutions were then 3D printed to obtain corresponding PLA scaffolds, each scaffold with a thickness of 3.2mm and dimensions of 8mm in both length and width. 100mg of each PLA scaffold was then treated in 20mL of etching solutions of 500mM hydrochloric acid, sodium hydroxide, and ammonia at 45℃ for 24 hours. Figure 6 As shown, the porosity of the above-mentioned scaffolds was calculated by tomographic scanning. The polylactic acid scaffold with added sodium bicarbonate particles showed the best porosity after hydrochloric acid etching.

[0048] Example 6: Tomographic characterization of lactic acid scaffolds incubated with different aqueous etching solutions

[0049] Four 5mg portions of racemic polylactic acid (PLA) material (50kDa) were dissolved in 20mL of dichloromethane, and 5mg of ground sodium bicarbonate particles were added. The mixtures were stirred at 20℃ for 6 hours and then dried in an oven at 60℃ for 3 hours to obtain four PLA stock solutions. These four PLA stock solutions were then 3D printed to obtain corresponding sodium bicarbonate-modified PLA scaffolds. The scaffolds had a thickness of 3.2mm and dimensions of 8mm in both length and width. PLA scaffolds prepared without sodium bicarbonate particles were used as a control group. 100mg of sodium bicarbonate-modified PLA scaffolds were then treated in 20mL of etching solutions of 100, 200, 500, and 1000mM hydrochloric acid at 45℃ for 24 hours. Figure 7 As shown, the porosity of the scaffold was calculated by tomographic scanning. The porosity of the polylactic acid scaffold without sodium bicarbonate particles was 51%. As the concentration of hydrochloric acid used for etching increased, the porosity of the scaffold continued to increase, with the highest porosity after etching at 500 and 1000 mM.

[0050] Example 7: Nanoindentation instrument characterizes the mechanical strength of the stent

[0051] Two 5mg portions of racemic polylactic acid (PLA) material (50kDa) were dissolved in 20mL of dichloromethane. 5mg of ground sodium bicarbonate particles with a particle size of 50μm were added, and the mixture was stirred at 20℃ for 6 hours, followed by drying in a 60℃ oven for 3 hours to obtain two PLA stock solutions. The two PLA stock solutions were then 3D printed to obtain corresponding sodium bicarbonate-modified PLA scaffolds. The scaffolds had a thickness of 3.2mm and dimensions of 8mm in both length and width. A PLA scaffold prepared without sodium bicarbonate particles was used as a control group (referred to as a non-porous scaffold). Figure 8 Pore-forming scaffolds were obtained by first immersing 100 mg of sodium bicarbonate-modified polylactic acid scaffold in 20 mL of 500 mM hydrochloric acid etching solution at 45 °C for 24 h. Figure 8 The original scaffold was used; then 100 mg of sodium bicarbonate-modified polylactic acid scaffold was incubated in 20 mL of PBS aqueous solution (pH 7.4) at 750 rpm for 200 h, resulting in a scaffold with pores formed after 200 h of incubation in aqueous solution. Figure 8 As shown, the mechanical strength of the polylactic acid (PLA) scaffolds without pores, with pores, and with pores after incubation in aqueous solution for 200 h was calculated using a nanoindenter. The reduced modulus of the PLA scaffold without sodium bicarbonate particles was 8.01 GPa, and the hardness was 0.33 GPa. The reduced modulus of the PLA scaffold with pores containing sodium bicarbonate particles was 7.92 GPa, and the hardness was 0.36 GPa. The reduced modulus of the PLA scaffold with pores after incubation in aqueous solution for 200 h was 7.67 GPa, and the hardness was 0.37 GPa. This indicates that the PLA scaffolds obtained by our pore-forming method have good mechanical strength and stability.

Claims

1. A method for preparing a microporous 3D-printed polylactic acid scaffold, characterized in that, The method includes the following steps: Step 1: Add inorganic salt particles to the organic solution of polylactic acid and stir to obtain polylactic acid stock solution containing inorganic salt particles; Step 2: The polylactic acid stock solution is 3D printed to obtain a polylactic acid scaffold; the polylactic acid scaffold is incubated in an aqueous etching solution to obtain a microporous 3D printed polylactic acid scaffold.

2. The preparation method according to claim 1, characterized in that, The polylactic acid material includes one or more of dextrorotatory polylactic acid, levorotatory polylactic acid, racemic polylactic acid, and non-optically active polylactic acid; the molecular weight of the polylactic acid material is 10k-200k.

3. The preparation method according to claim 1, characterized in that, The organic solvent in the organic solution includes one or more of methanol, ethanol, acetonitrile, acetone, diethyl ether, N,N-dimethylformamide, dimethyl sulfoxide, and dichloromethane.

4. The preparation method according to claim 1, characterized in that, The inorganic salts include one or more of sodium chloride, calcium carbonate, copper sulfate, potassium nitrate, sodium bicarbonate, magnesium sulfate, iron oxide, calcium phosphate, and potassium chloride; the particle size of the inorganic salt particles is 10-50 μm.

5. The preparation method according to claim 1, characterized in that, The aqueous etching solution includes one or more of the following: hydrochloric acid, sulfuric acid, nitric acid, phosphoric acid, acetic acid, citric acid, sodium hydroxide, ammonia, magnesium hydroxide, sodium carbonate, sodium bicarbonate, sodium acetate, sodium hypochlorite, sodium phosphate, and sodium sulfite.

6. The preparation method according to claim 1, characterized in that, The ratio of polylactic acid material to organic solvent in the organic solution of polylactic acid is 0.1-20 mg: 20 mL; the ratio of polylactic acid scaffold after 3D printing to aqueous etching solution is 0.1-200 mg: 20 mL.

7. The preparation method according to claim 1, characterized in that, The concentration of the inorganic salt in the organic solution of polylactic acid is 0.1–20 mg / mL; the concentration of the aqueous etching solution is 1–2000 mM.

8. The preparation method according to claim 1, characterized in that, In the first step, the stirring treatment time is 1 to 96 hours; in the second step, the incubation time is 1 to 48 hours.

9. The preparation method according to claim 1, characterized in that, In the first step, the stirring temperature is 0–80°C, and in the second step, the incubation temperature is 0–60°C.

10. The microporous 3D printed polylactic acid scaffold prepared by the preparation method according to claim 1.